ANALISIS STRATEGI SMK3 BERKELANJUTAN DENGAN PENDEKATAN SWOT PADA KONTRAKTOR LISTRIK DI PADANG - Primayota, Riren; Carlo, Nafryzal; Heldi, Heldi (Rang Teknik Journal, 2025)
The lack of workers' understanding of the importance of OHS (Occupational Health and Safety) contributes to the high rate of workplace accidents in electrical projects. This study aims to identify internal and external factors affecting the implementation of OHS Management Systems (SMK3) among electrical contractors and to formulate strategies using SWOT analysis. Data was collected through observations and questionnaires, then analyzed using IFAS, EFAS, IE Matrix, and SWOT.The IE Matrix results indicate that the company is in the "Growth and Build" category with an IFAS score of 3.8835 and an EFAS score of 4.0000, reflecting significant external pressures and opportunities for growth. Recommended strategies include improving SMK3 practices and intensifying SMK3 program development. SWOT strategies include: (1) S-O Strategy: enhancing SMK3 implementation and increasing workforce competency; (2) W-O Strategy: providing OHS training for workers; (3) S-T Strategy: conducting education and outreach on SMK3 implementation; and (4) W-T Strategy: developing detailed and strict OHS regulations. This approach aims to reduce workplace accidents.Keywords: Implementation Strategy, SMK3, IFAS, EFAS, SWOT